Seeking Impact and Visibility Scholarly Communication in Southern Africa - Trotter, Henry; King, Thomas (Research Assistant); Gray, Eve Horwitz; Willmers, Michelle; Kell, Catherine; University of Cape Town. Scholarly Communication in Africa Programme; Project Muse; Project Muse. (Project Muse, 2014)
African scholarly research is relatively invisible globally because even though research production on the continent is growing in absolute terms, it is falling in comparative terms. In addition, traditional metrics of visibility, such as the Impact Factor, fail to make legible all African scholarly production. Many African universities also do not take a strategic approach to scholarly communication to broaden the reach of their scholars' work. To address this challenge, the Scholarly Communication in Africa Programme (SCAP) was established to help raise the visibility of African scholarship by mapping current research and communication practices in Southern African universities and by recommending and piloting technical and administrative innovations based on open access dissemination principles. To do this, SCAP conducted extensive research in four faculties at the Universities of Botswana, Cape Town, Mauritius and Namibia.
Executive summary -- Programme overview -- Project components and methodology -- The Southern African university context -- Scholarly communication policy landscape in Southern Africa -- Research and communication practices -- The SCAP implementation initiative -- Challenges, contradictions and opportunities -- Key findings -- Recommendations -- References.
Issued as part of book collections on Project MUSE.
Includes bibliographical references (pages 237-246).
Description based on print version record.
Keywords: Universities and colleges -- Africa, Southern; Research -- Publishing -- Africa, Southern; Open access publishing -- Africa, Southern; Scholarly publishing -- Africa, Southern; Communication in learning and scholarship -- Technological innovations -- Africa, Southern; Communication in learning and scholarship -- Africa, Southern; Electronic books; Electronic books